IMPLEMENTASI PROGRAM JEMPUT BOLA DALAM PEMBUATAN AKTA KELAHIRAN DISDUKCAPIL KABUPATEN KETAPANG - E1012171008 Munad Ziroh; Hardilina Hardilina; Ida Rochmawati (FISIP Universitas Tanjungpura, 2020)
This research aims to give understanding about the implementation of proactive service in making birth certificate worked by Civil Registry Service Office of Ketapang Regency. The issue related to the birth certificate happening in this area was quiet interesting to be researched if we take consideration to many resistances toward the implementation of this proactive service program. The implementation of this proactive program in making birth certificate in Ketapang Regency has been the responsibility of Civil Registry Service Office of Ketapang Regency. This program was implemented in order to achieve the maximum level of birth certificate ownership so that people could accept their rights completely as Indonesian citizens although there are still limited access of infrastructures and resources. The main problem of this research was because the communication between Civil Registry Service Office and the people in delivering information about the proactive program was not optimal yet. Besides, the facilities and infrastructures such as record equipment and transportation were limited, also small number of human resources and staffs were available. This research used the theory of public policy implementation by George C. Edward III about supporting and resistor factors related to policy, which include communication, resources, disposition and bureaucracy hierarchy.